POLA PEMBERDAYAAN PEGAWAI NEGERI SIPIL DALAM PELAKSANAAN TUGAS ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN LAMPUNG TENGAH - Sigit Setioko (Derivatif : Jurnal Manajemen, 2017)
Charges against qualified employees getting stronger so that the implementation of empowerment in developing HR competencies of civil servants in the Secretariat of the Regional Representatives Council (DPRD)Central Lampungregency had not negotiable. But employees do not seem to understand and carry out their duties and functions, some are employees who understand their duties and functions, but does not perform the job optimally, even some employees consider coming late to the office are common, and they often employees are not present without explanation. The research problem is formulated as follows: "How Patterns Empowerment of Civil Servants in the discharge of members of the House of RepresentativesCentral Lampungdistrict?".Research carried out by methods descriptive-qualitative data collection techniques such as interviews, documentation, and observation. Information is determined not only of employees but also from legislatorsCentral Lampungregency.This study concluded: (1) Pattern empowerment of civil servants deemed appropriate Parliament Secretariat is being implemented consistently, in accordance with the conditions of employment and implemented fully. (2) The firmness of a leader or supervisor to employees with low performance or an employee with poor discipline so far is enough to affect the attitude improvement and increased productivity. (3) Modeling of the leaders of the secretariat of Central Lampung Regency very important role in empowering civil servants. (4) Empowerment of civil servants should not only emphasize the improvement of skills and knowledge of employees, but also to build character and personality of the civil servants who are responsible.